Characteristics of referred patients to the Emergency Department in Aceh before COVID-19 pandemic - Meilya Silvalila; Nurul Huzaifi; Shefina Pyeloni Harnold; Reza Akbar (Trends in Infection and Global Health, 2022)
As an important entry point for referral patients, the management of the Emergency Department to care and implement the best possible treatment are required. The Emergency Department of provincial hospital plays a vital role as a referral hospital of all district-level hospitals to provide initial treatment for a broad spectrum of illnesses and injuries. In Aceh, many referral issues were encountered at the Emergency Department of Dr. Zainoel Abidin Hospital, which categorized the referral patient's condition that was considered to improve clinical care to patients referred. This quantitative study aims to determine the characteristics of patient referral and the referral issues encountered at the Emergency Department of dr. Zainoel Abidin. In total, 1674 patients were recruited using the purposive sampling method from April to June 2019. The results showed that most referral patients arrived at the Dr. Zainoel Abidin Hospital emergency room during the night and very few arrived in the morning. Most patients arriving at the Emergency Department of Dr. Zainoel Abidin Hospital at night were from Aceh Singkil and Gayo Lues. Meanwhile, patients from Aceh Besar, Aceh Jaya, Banda Aceh, Pidie, and Pidie Jaya mostly arrived at the Emergency Department Dr. Zainoel Abidin Hospital during the afternoon. Most patients from Sabang and Simeulu came in the morning. The most commonly referred patients were adult and elderly patients, aged 46-65 years. Most of the patients had been treated in the daycare unit at the previous hospitals with the longest hospital stay was 36 days before being referred to Dr. Zainoel Abidin Hospital. Head injuries and strokes were the most frequent diagnosis led to Emergency Department Dr. Zainoel Abidin Hospital. Furthermore, our study found that 51% of the referral care system issue was that the patient did not arrive at the Emergency Department of Dr. Zainoel Abidin Hospital after being confirmed to be referred through telephone. Most of this issue happened in June for an unknown reason. At the same time, another 23% was due to the unavailability of intensive care.